Animal, Vegetable, Digital : Experiments in New Media Aesthetics and Environmental Poetics - Swanstrom, Elizabeth, 1974- (Book collections on Project MUSE., 2016)
"In Animal, Vegetable, Digital, Elizabeth Swanstrom makes a confident and spirited argument for the use of digital art in support of ameliorating human engagement with the environment and suggests a four-part framework for analyzing and discussing such applications. Through close readings of a panoply of texts, artworks, and cultural artifacts, Swanstrom demonstrates that the division popular culture has for decades observed between nature and technology is artificial. Not only is digital technology not necessarily a brick in the road to a dystopian future of environmental disaster, but digital art forms can be a revivifying bridge that returns people to a more immediate relationship to nature as well as their own embodied selves. To analyze and understand the intersection of digital art and nature, Animal, Vegetable, Digital explores four aesthetic techniques: coding, collapsing, corresponding, and conserving. "Coding" denotes the way artists use operational computer code to blur distinctions between the reader and text, and, hence, the world. Inviting a fluid conception of the boundary between human and technology, "collapsing" voids simplistic assumptions about the human body's innate perimeter. The process of translation between natural and human-readable signs that enables communication is described as "corresponding." "Conserving" is the application of digital art by artists to democratize large- and small-scale preservation efforts. A fascinating synthesis of literary criticism, communications and journalism, science and technology, and rhetoric that draws on such disparate phenomena as simulated environments, video games, and popular culture, Animal, Vegetable, Digital posits that partnerships between digital aesthetics and environmental criticism are possible that reconnect humankind to nature and reaffirm its kinship with other living and nonliving things."--Publisher's description